Arterial stiffness determined according to the cardio-ankle vascular index is associated with paroxysmal atrial fibrillation: a cross-sectional study. Issue 1 (2nd May 2014) - Miyoshi, Toru; Doi, Masayuki; Noda, Yoko; Ohno, Yuko; Sakane, Kosuke; Kamikawa, Shigeshi; Noguchi, Youko; Ito, Hiroshi
Abstract : Background: Several lines of evidence suggest that atrial fibrillation (AF) may be a consequence of vascular disease. We investigated the relationship between cardio-ankle vascular index (CAVI), a new index of arterial stiffness, and the presence of paroxysmal AF (PAF). Methods and results: 181 outpatients (91 patients with PAF and 90 age- and gender-matched subjects without PAF) were analysed for their sinus rhythm. The CAVI was significantly higher in patients with PAF than in subjects without PAF (9.0±1.0 vs 8.7±0.8, p<0.01). In all subjects, the CAVI was significantly correlated with the left ventricular mass index (r=0.30, p<0.01), left atrial diameter (r=0.22, p<0.01), and augmentation index, a parameter of wave reflection (r=0.32, p<0.01), in addition to age, systolic blood pressure and pulse pressure. Logistic analysis demonstrated that the CAVI was independently associated with PAF even after adjustment for confounding factors. The adjusted OR of PAF was 1.8 for each unit increase in the CAVI (p=0.01). Conclusions: Our finding suggests that increased arterial stiffness may be involved in the maintenance of AF.